Motor Function Relating to the Accuracy of Self-Overestimation Error in Community-Dwelling Older Adults - Kawasaki, Tsubasa; Tozawa, Ryosuke (Frontiers in Neurology, 2020)
Background: The self-overestimation of motor performance is a serious safety hazard concerning older adults. However, the cause of self-overestimation remains to be fully established. Thus, the present study aimed to reveal the factors associated with self-overestimation by focusing on motor function. Methods: One hundred five community-dwelling older adults (20 males, median (25, 75 percentile) age: 73.00 (69.50, 77.50)) participated. They were assessed on self-estimation error using a two-step test. They estimated the two-step distance that would be reached with maximum effort. Thereafter, they performed the actual two-step. Participants were also comprehensively assessed on motor functions by various tests (i.e., 10-meter Walking Test, Timed Up and Go Test, postural stability, and muscle strength). Participants were divided into two groups (the self-underestimation or self-overestimation group) and their motor performances were compared. Then, multiple linear regression analysis was utilized to investigate the relationship between self-estimation error and motor function. Results: Significant differences were found between the two groups regarding age, weight, actual two-step distance, and the time required for the Timed Up and Go Test and 10-meter Walking Test (p < 0.05). The regression analysis showed that self-estimation error was significantly related to the result of the 10-meter Walking Test (beta = 0.24, p = 0.011). Conclusions: Self-overestimation of motor performance, which is likely to lead to several dangers (i.e., falling or obstacle collision), was related to walking ability. Consequently, the results showed that the 10-meter Walking Test would assist in detecting the self-overestimation of one’s own motor performance.